Odpowiedź:
[tex]9.(64x^3y^6):(8x^3y^2)^2=(64x^3y^6):(64x^6y^4)=\frac{64x^3y^6}{64x^6y^4}=\frac{y^{6-4}}{x^{6-3}}=\frac{y^2}{x^3}\\\\dla\ \ x=2\ \ i\ \ y=\sqrt{2}\\\\\\\frac{y^2}{x^3}=\frac{(\sqrt{2})^2}{2^3}=\frac{2}{8}=\frac{1}{4}\\\\\\10.\\\\\dfrac{\sqrt{0,5}:\sqrt{0,005}}{(-0,1)^2}+\dfrac{2\sqrt[3]{0,4}}{\sqrt[3]{3,2}}=\dfrac{\sqrt{0,5:0,005} }{(\frac{1}{10})^2}+2\sqrt[3]{\frac{0,4}{3,2}}=\dfrac{\sqrt{100}}{\frac{1}{100}}+2\sqrt[3]{0,125}=[/tex]
[tex]=\dfrac{10}{\frac{1}{100}}+2\sqrt[3]{0,125}=10:\frac{1}{100}+2\sqrt[3]{\frac{1}{8}}=10\cdot100+\not2\cdot\frac{1}{\not2}=1000+1=1001\\\\\\Odp.A[/tex]